Effect of Electrical Stimulation in Lower Extremity as Physical Exercise in Type 2 Diabetes Mellitus Patients - Rika Wahyuni Arsianti; Dewy Haryanti Parman; Hendy Lesmana; Muhammad Taufiqqurohman (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Type 2 diabetes mellitus (T2DM) is a long-term illness that affects the patient's quality of life and requires substantial health care costs. Lifestyle relatedto physical exercise is one of the causes of the increasing prevalence of this disease. However, not all T2DM patients can perform physical exercise because very weak physical conditions such as elderly, spinal cord injury or diabetic secondary complications can be contraindicated when physical exercise performed. The aim of this study is to observe the used of electrical stimulation in T2DM patients.METHODS: The provision of ES to lower extremity muscles was given for 30 minutes in the intervention group. Blood glucose samples were taken before and after the ES intervention. The data collected was statistically analyzed by using paired T-test and expressed in mean±standard error.RESULTS: The ES intervention decrease blood glucose level significantly from 193.03±5.740 mg/dL to 170.66±5.200 mg/dL (p≤0.001) in the last session.CONCLUSION: The effect of ES in lower extremity is shown to be significantly lowers the blood glucose level in T2DM patients.KEYWORDS: blood glucose, electrical stimulation, physical exercise, type 2 diabetes mellitus